Improving Care for Elders Who Prefer Informal Spaces to Age-Separated Institutions and Health Care Settings. Issue 3 (22nd July 2019) - Torres, Stacy; Cao, Xuemei
Abstract: Background and Objectives: Despite advantages of urban areas (such as walkability, public transportation, nearby shopping, and health care services), challenges remain for elders aging in place to access care. The changing demographics of older adults, with higher rates of divorce, singlehood, and childlessness, often living alone and far from family, necessitate new strategies to support health and well-being. Research Design and Methods: Drawing on 5 years of ethnographic fieldwork and 25 interviews with elders in New York City, this study presents empirical insights into older adults' use of "third places" close to home, in conjunction with more formal settings. Results: This article identifies external and internalized ageism and complicated age-based identity as important reasons why older adults preferred "third places" to age-separated spaces such as senior centers and formal settings such as health care settings. We find that neighborhood "third places" offer important physical venues for older adults to process negative or hurried interactions in other formal and age-separated places. Discussion and Implications: This article makes policy suggestions for increasing access and usage of essential services, including developing attractive and appealing intergenerational spaces in which older community members can obtain services and dispatching caseworkers to public spaces where elders congregate. Furthermore, this article recommends improving exchanges between health care providers and older adults so that they feel recognized, respected, and cared for, which can improve health care outcomes.